A Computer-based Role-Playing Game for Participatory Management of Protected Areas: The SimParc Project - Briot, Jean-Pierre; Vasconcelos, Eurico; Adamatti, Diana; Sebba, Vinícius; Irving, Marta; Barbosa, Simone; Furtado, Vasco; Lucena, Carlos (Anais do Seminário Integrado de Software e Hardware (SEMISH), 2008)
This paper shows an example of how role playing games can be used for two complementary purposes: to help at extracting the expertise of social actors, but also to support their participation in decision making. These two objectives correspond, respectively, to the 2nd grand challenge (computational modeling of complex systems) and to the 4th one (participatory access to knowledge). Our approach combines distributed role playing, geographic information systems, support for player negotiations and insertion of various types of artificial agents. We are exploring it in the context of participatory management of protected areas, for biodiversity conservation and social inclusion.